Implementation of Kinesics and Proxemics In The Rhetoric of Da’wah - Rahman, Taufik; Indriati, Anisah (UIN Fatmawati Sukarno Bengkulu, 2024)
Communication and conveying messages through language are not static aspects but dynamic ones. Verbal communication will become static if it ignores nonverbal elements in its implementation practice. For this reason, dynamism is needed when conveying a communication message. The dynamics present are due to the involvement of nonverbal communication elements such as kinesics and proxemics. The integration of the involvements of both, namely verbal and nonverbal, in various aspects is very prominent during the communication process, such as what occurs in the rhetorical process of da'wah. This study examines the application of proxemics and kinesics, two forms of nonverbal communication, in the preaching of rhetoric. This research uses a qualitative approach by analyzing relevant references regarding kinesics, proxemics, and preaching rhetoric and looking at the relevance of their implementation in preaching rhetoric. The results of this research reveal that kinesics and proxemics are a